The tower treasure - Dixon, Franklin W. (New York : Grosset & Dunlap, 1959)
After a dying criminal confesses that his loot has been stashed "in the tower," the Hardy boys make an astonishing discovery.
Keywords: Mystery -- Juvenile Fiction